Negotiating Gender Expertise in Environment and Development Voices from Feminist Political Ecology - Resurrección, Bernadette P.; Elmhirst, Rebecca (Routledge Studies in Gender and Environments, 2020)
"This book casts a light on the daily struggles and achievements of 'gender experts' working in environment and development organisations, where they are charged with advancing gender equality and social equity and aligning this with visions of sustainable development. Developed through a series of conversations convened by the book's editors with leading practitioners from research, advocacy and donor organisations, this text explores the ways gender professionals - specialists and experts, researchers, organizational focal points - deal with personal, power-laden realities associated with navigating gender in everyday practice. In turn, wider questions of epistemology and hierarchies of situated knowledges are examined, where gender analysis is brought into fields defined as largely techno-scientific, positivist and managerialist. Drawing on insights from feminist political ecology and feminist science, technology and society studies, the authors and their collaborators reveal and reflect upon strategies that serve to mute epistemological boundaries and enable small changes to be carved out that on occasions open up promising and alternative pathways for an equitable future. This book will be of great relevance to scholars and practitioners with an interest in environment and development, science and technology, and gender and women's studies more broadly."